Fear of Missing Out Syndrome and its Impact on Sleep Quality in Medical Students: A Cross-sectional Study - Oliveira, Jullyane Laysa de Carvalho; Carvalho Neta, Otília Jurema de; Athayde, Rodolfo Augusto Bacelar de (Sleep Science, 2024)
Objective Fear of missing out (FOMO) is a type of social anxiety defined as “intense concern that others may be experiencing rewarding experiences without one's presence,” which can lead to illness. Excessive smartphone use is often associated with FOMO. This study aimed to investigate FOMO among medical university students, as well as factors associated with sleep quality, anxiety, depression, and excessive smartphone use.Materials and Methods A cross-sectional observational study was conducted using electronic questionnaires and the following scales: FOMO scale/score, Pittsburgh Sleep Quality Index (PSQI), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and Smartphone Addiction Scale Short Version (SAS SV).Results Participants included 142 individuals (mean age 23.73 ± 4.98 years, 97 [68.3% female]). All participants were smartphone users. Fear of missing out was present (FOMO score 22.08 ± 6.71) along with poorer sleep quality (PSQI 7.26 ± 3.08) and excessive smartphone use (SAS SV 30.21 ± 10.20). Moderate/severe anxiety (BAI) was reported by 35.2% of participants, while 16.9% had moderate/severe depression (BDI). Positive correlations were found between PSQI and FOMO (p < 0.05), as well as between SAS SV and FOMO (p < 0.001), PSQI (p < 0.001), BAI (p < 0.001), and BDI (p < 0.001).Discussion High levels of FOMO, poorer sleep quality, symptoms of depression, anxiety, and excessive smartphone use were found among medical students. Furthermore, a positive correlation was demonstrated between these factors, which can directly impact the physical and mental health, as well as the academic performance of these young individuals.
Keywords: sleep; quality of life; anxiety; depression; smartphone; social media